Hubungan Lama Penggunaan Smartphone dengan Perilaku Sosial Anak Usia Dini di TK Aisyiyah Ciputat-Tangerang Selatan - Siti Zahara Harahap; Herry Susanto; Indra Tri Astuti (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The rapid advancement of digital technology has led to a significant increase in smartphone use among early childhood populations, which may potentially influence social behavior development during the critical golden age. This study aimed to analyze the relationship between the duration of smartphone use and the social behavior of early childhood students at Aisyiyah Kindergarten, Ciputat–South Tangerang. This research employed a non-experimental quantitative design with a correlational approach. Data were collected using questionnaires. The study involved 48 respondents selected through a total sampling technique. The collected data were statistically analyzed using the Spearman rank correlation test. The results showed that most respondents were 4 years old (45.8%) and male (60.4%). The majority of children demonstrated low levels of social behavior (58.3%) and high levels of smartphone use duration (56.3%). Statistical analysis revealed a significant relationship between the duration of smartphone use and social behavior in early childhood (p-value = 0.000). Thus, it can be concluded that there is a significant association between smartphone use duration and the social behavior of early childhood students at Aisyiyah Kindergarten, Ciputat–South Tangerang.